A Bakhtinian reading of Disney's reciprocal relationship with its critics since Snow White (1937) in the light of a comparative analysis of Pocahontas (1995) and Moana (2016). - İncegül, Gizem (İstanbul Bilgi Üniversitesi, 2019)
Women and racial minorities have been fighting for their initial human rights for decades, and where are we now? In an urge to find “one of the reasons why”, this study shifts back to childhood and focuses on children’s animated movies by Disney, a harshly criticized company for promoting stereotypes. In addition to a critical discourse analysis, this study also acquires an -almost- affirmative approach upon an alleged reconciliation of the company with its critics and toning down sexism and racism in its contents. This reciprocal relationship requires a Bakhtinian reading on the basis of his concepts of Addressivity and Responsivity. Moreover, each criticism is matched with the target movie and what the company does/ whether it changes the criticized features in the following production or not is analysed. As a result, it was found that Disney tries to give a proper response to the criticisms it receives. Moreover, filling a gap in the existing knowledge, another aim of this thesis is to pursue the reason why Disney promotes bias for decades. Pursuing the motive behind, both sociopolitical atmospheres in which animated movies were released and CEO’s managing the company at the time are investigated. While the atmospheres of each era does not justify Disney’s attitude, it was concluded that the management holds a greater power over the productions and the messages they convey.

Kadınlar ve azınlıklar yıllardır temel insan hakları için savaş veriyor, peki bugün neredeyiz? Bugünkü durumun sebeplerinden yalnızca birini bulma arayışındaki bu çalışma çocukluğa odaklanarak, Disney’in bu hedef kitleye yönelik hazırladığı animasyon filmlerine odaklanıyor. Söylem analizinin yanı sıra bu çalışmada, söz konusu şirketin yıllardır aldığı eleştiriler akabinde yönelebileceği bir uzlaşı sürecine de, olumlamacı bir bakış açısıyla yaklaşılıyor. Disney’in içeriklerindeki cinsiyetçi ve ırkçı söylemleri azalttığı bu süreç, Mihail Bahtin’in teorisinden Addressivity ve Responsivity yani “hitap” ile “cevaplılık” konseptlerinin ışığında inceleniyor. Şirketin aldığı her bir eleştiri, hedeflenen film ile eşleştirilerek Disney’in bir sonraki yapımında bu özellikleri değiştirip değiştirmediği inceleniyor. Sonuç olarak, Disney’in mevcut eleştirilere cevap vermeye çalıştığı saptanıyor. Bunun yanı sıra, bu çalışma, mevcut literatürdeki bir boşluğu doldurma gayesiyle Disney’in yıllar boyunca ayrımcı dili yaymış olmasının ardındaki sebebi de araştırıyor. Bunun ardındaki motivasyonu arayan çalışmada her bir filmin yayımlandığı yıldaki sosyo-politik atmosfer ile şirketi bugüne dek yönetmiş üç farklı yönetim kurulu başkanı, muhtemel bir mazeret olarak ele alınıyor. Günün gerekleri Disney’in yaklaşımını aklamada yetersiz kalsa da, yönetim kurulu başkanlarının, animasyonların verdiği ya da vermeye çalıştığı mesajlar üzerinde etkili olduğu sonucuna varılıyor.
Pocahontas(1995) ve Moana'nın (2016) karşılaştırılmalı incelemesi ışığında Snow White'tan(1937) bu yana Disney'in eleştirmenleriyle karşılıklı ilişkisinin Bakhtin'in teorisiyle incelenmesi